Investigating the Use of Corpus-Informed Grammar Materials in Indonesian EFL Classrooms - Ikmi Nur Oktavianti; Efit Eriani; Ifa Rolyna; Icuk Prayogi (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Despite the growing recognition of corpus in language teaching and learning, the importance of teaching materials informed by corpus investigation has not been widely acknowledged, especially in the EFL context. In teaching grammar, it is essential to provide authentic materials for the learners indicating both grammaticality and appropriateness. This study investigates students’ perceptions of the use of corpus-informed grammar materials and the strengths and drawbacks of these materials. The participants were 40 Basic Structure students at their first-year university level. The data were collected using questionnaires and interviews after the participants attended seven meetings with Real Grammar as the book used in the classroom. The data were then coded, categorized, and analyzed to describe how the students perceived the materials. The present study showed that most students have a positive attitude toward the corpus-informed grammar book since it enables them to know the appropriate context of use related to the register (spoken or written). Corpus-informed materials have several strengths, such as describing the register-specific and frequency information, improving language learning awareness, learning motivation, critical thinking, and many more. However, corpus-informed materials should not be the only thing to rely on, so lecturers or instructors should provide adequate explanations for the materials and corpus research. These results show that it is necessary to promote the use of corpus-informed materials in EFL classrooms, including grammar classes. However, the teachers should also be trained on how corpus works, and corpus-related terms and the use of corpus-informed materials should be reconsidered for the lower level of learners.